Sarcoidosis Presenting as a Giant Pulmonary Bulla With Concurrent COVID-19 Infection - Sathish Krishnan MD, FCCP; Anam Naumaan MD; Venu Pararath Gopalakrishnan MD, FACP (Journal of Investigative Medicine High Impact Case Reports)
Sarcoidosis is a systemic granulomatous disease that predominantly affects the lungs. However, its presentation as a giant pulmonary bulla is exceptionally rare. Its association with COVID-19 has raised new concerns regarding disease exacerbation and misdiagnosis. We report a case of a 38-year-old man who developed a large left lower lobe bulla in the context of recent COVID-19 infection. Initial misinterpretation of the bulla as loculated pneumothorax nearly led to an unnecessary chest tube placement. A subsequent thoracotomy with lobectomy revealed nonnecrotizing granulomas, confirming sarcoidosis. The patient showed spontaneous remission without requiring treatment. This case highlights the importance of multidisciplinary discussions in atypical lung presentations to prevent mismanagement.